Des normes professionnelles à caractère doxique aux difficultés de mise en œuvre de séquences d'investigation en classe de sciences : comprendre les déterminations de l'action - Corinne Marlot; Ludovic Morge (Nantes Université, 2015)
A study of the literature shows that teachers find it extremely difficult to implement inquiry-based experimental science education. The reasons for this are generally thought in the individual characteristics of the teachers themselves: their epistemological beliefs, the way they relate to their subject, or the insufficiently sound subject knowledge. In this paper, we shall explore another avenue, namely doxic professional norms. It would seem that these norms are shared by teachers, and are rooted in principles coming from primary (national curriculum and guidelines) and secondary (training and school textbooks) instructions. It is this that gives them their legitimacy.We shall begin by a hypothetical formulation of these norms, so that these can then be used in order to analyse and interpret the difficulties a nursery school teacher has in implementing inquiry-based science education. Finally, we shall discuss how these norms can be taken into account in teacher training, and what research still needs to be done in order to confirm the existence of these norms, and the role they play in determining teacher activity.